Double-rooted primary canines: A report of three cases - Orhan Ayse; Sari Saziye (Wolters Kluwer Medknow Publications, 2006)
This article reports three rare cases of birooted primary canines. In one of the three cases reported, the double-rooted primary canine was unilateral, which is a unique condition in the dental literature. One of the birooted primary canines was extracted for examination. Root canal morphology was examined using the clearing technique and three root canals were detected. The detection of birooted teeth requires a fastidious radiographic evaluation. Moreover, it should be kept in mind during endodontic therapy that the number of root canals might exceed the number of roots for these teeth.